Mother's exercise during pregnancy programmes vasomotor function in adult offspring. Issue 1 (4th December 2013) - Bahls, Martin; Sheldon, Ryan D.; Taheripour, Pardis; Clifford, Kerry A.; Foust, Kallie B.; Breslin, Emily D.; Marchant‐Forde, Jeremy N.; Cabot, Ryan A.; Harold Laughlin, M.; Bidwell, Christopher A.; Newcomer, Sean C.
New Findings What is the central question of this study? Adverse maternal behaviour during pregnancy is well known to have lifelong health consequences for offspring. We asked whether a positive maternal health behaviour may have positive long‐term effects for offspring. Specifically, we investigated whether aerobic maternal exercise improves nitric oxide signalling in femoral arteries of adult swine. What is the main finding and its importance? For the first time, a fetal programming outcome due to gestational exercise is reported in adult offspring. Second, contrary to previous speculation regarding the impact of in utero alterations on nitric oxide signalling, our data suggest differential myosin phosphorylation in vascular smooth muscle. The intrauterine environment is influenced by maternal behaviour and programmes atherosclerotic disease susceptibility in offspring. The aim of this investigation was to test the hypothesis that mothers' exercise during pregnancy improves endothelial function in 3‐, 5‐ and 9‐month‐old porcine offspring. The pregnant sows in the exercise group ran for an average of 39.35 ± 0.75 min at 4.81 ± 0.35 km h−1 each day for 5 days per week for all but the last week of gestation. This induced a significant reduction in resting heart rate (exercised group, 89.3 ± 3.5 beats min−1; sedentary group, 102.1 ± 3.1 beats min−1; P < 0.05) but no significant differences in gestational weight gain (65.8 ± 2.1 versus 63.3 ± 1.9%). No significant effect on bradykinin‐induced vasorelaxation with and without l‐NAME was observed. A significant main effect was identified on sodium nitroprusside‐induced vasorelaxation (P= 0.01), manifested by a reduced response in femoral arteries of all age groups from exercised‐trained swine. Nitric oxide signalling was not affected by maternal exercise. Protein expression of MYPT1 was reduced in femoral arteries from 3‐month‐old offspring of exercised animals. A significant interaction was observed for PPP1R14A (P < 0.05) transcript abundance and its protein product CPI‐17. In conclusion, pregnant swine are able to complete an exercise‐training protocol that matches the current recommendations for pregnant women. Gestational exercise is a potent stimulus for programming vascular smooth muscle relaxation in adult offspring. Specifically, exercise training for the finite duration of pregnancy decreases vascular smooth muscle responsiveness in adult offspring to an exogenous nitric oxide donor.